Factors related to the spontaneous passage of common bile duct stones through the papilla: a single-center retrospective cohort study. Issue 11 (November 2021) - Ding, Songming; Dong, Shanjie; Zhu, Hengkai; Wu, Weilin; Hu, Yiting; Li, Qiyong; Zheng, Shusen
Objective: Common bile duct (CBD) stones can spontaneously pass through the papilla. This study explored factors associated with stone passage by comparing differences in the clinical features of stones retained in the CBD and excreted stones. Methods: Data were retrospectively collected for all patients who were hospitalized in our center between March 2016 and May 2021 with clinical, laboratory, or imaging evidence of CBD stones. All patients underwent endoscopic retrograde cholangiopancreatography (ERCP) and were classified into two groups: group A (stones extracted by ERCP, n  = 86) and group B (stones discharged before ERCP, n  = 15). Demographic data, biochemical and radiological findings were compared between the groups. Results: Stone size (0.82 vs. 0.33 cm), and levels of total bilirubin (58.2 vs. 28.8 μmol/L), gamma-glutamyl transpeptidase (416.7 vs. 193.9 U/L), alkaline phosphatase (191.9 vs. 123.1 U/L), carbohydrate antigen 19-9 (603.7 vs. 37.2 U/mL), and α-L-fucosidase (37.4 vs. 22.6 U/L) were significantly higher in group A than in group B. Logistic regression analyses showed that stone size was the only factor significantly associated with spontaneous passage of CBD stones. Conclusions: CBD stones less than 0.33 cm in size may be self-expelled through the papilla.